The Predictive Competing Endogenous RNA Regulatory Networks and Potential Prognostic and Immunological Roles of Cyclin A2 in Pan-Cancer Analysis - Chen, Shenyong; Zhao, Zhijia; Wang, Xiaobo; Zhang, Qi; Lyu, Li; Tang, Bo (Frontiers in Molecular Biosciences, 2022)
Although accumulating evidence has verified the relationship between CCNA2 and cancers, no pan-cancer analysis about the function and the upstream molecular mechanism of CCNA2 is available. For the first time, we analyzed potential oncogenic roles of CCNA2 in 33 cancer types via The Cancer Genome Atlas (TCGA) database. Overexpression of CCNA2 was widespread in almost all cancer types, and it was related to poor prognosis and worse pathological stages in most cases. Moreover, we conduct upstream miRNAs and lncRNAs of CCNA2 to establish ceRNA networks in kidney renal clear cell carcinoma (LINC00997/miR-27b-3p/CCNA2), liver hepatocellular carcinoma (SNHG16, GUSBP11, FGD5-AS1, LINC00630, CD27-AS1, LINC00997 and TTC28-AS1/miR-22-3p/CCNA2, miR-29b-3p/CCNA2, miR-29c-3p/CCNA2, and miR-204-5p/CCNA2) and lung adenocarcinoma (miRNA-218-5p/CCNA2 and miR-204-5p/CCNA2) by expression analysis, survival analysis, and correlation analysis. CCNA2 expression was positively correlated with Th2 cells infiltration, and negatively correlated with CD4+ central memory and effector memory T Cells infiltration. Furthermore, CCNA2 was positively associated with expressions of immune checkpoints (CD274, PDCD1 and CTLA4) in most cancer types. Our first CCNA2 pan-cancer study contributes to understanding the prognostic and immunological roles and potential upstream molecular mechanism of CCNA2 in different cancers.